Attitudes Concerning Extended Teacher Education Programs: A Rural/Urban Comparison - Kay S. Bull; Michael M. Warner; David Yellin; Donald W. Robinson; Gay C. Neuberger (Journal of Research in Rural Education, 1988)
Stimulated by changes proposed by the Holmes and Carnegie reports, this study was conducted to assessthe attitudes of rural and urban teacher educators and graduate students toward extended teacher education programs. Data were collected from faculty and graduate students affiliated with 44 teacher preparation institutions in the south-central region of the United States. Lessthan one-fourth of the entire sample expressed consistent support for extending the programs. Lessthan a third of the sample favored the expansion of the liberal arts component of teacher education programs. Within the framework of extended programs, over half of the sample favored increasing professional coursework and more than seventy percent favored increased field experiences. Lessthan 10%thought that their own teacher education had been inadequate, again indicating support for existing four-year programs. Rural/urban comparisons showed that faculty and students in urban areas were generally more supportive of the types of changes recommended in the Holmes and Carnegie reports. Implications for rural education, rural teacher education, and possible outcomes in a time of projected teacher shortages are explored.